Effect of spray characteristics influences combustion in DI diesel engine – A review. (2020) - Gopinath, S.; Devan, P.K.; Sabarish, V.; Sabharish Babu, B.V.; Sakthivel, S.; Vignesh, P.
Abstract: In a DI Diesel Engine performance, emission and combustion characteristics, spraying behaviour plays a vital role. Emerging research in new fuels is increasing day by day, to find the best fuel in light of the combustion characteristics. It is mandatory to study about effects of spray behavior, droplet growth and the formation of new droplets. The aim of this review is to compare the spray characteristics of diesel engines under various ambient conditions. It can be inferred that if the incident primary sprays developed have a generalized kind of size distribution, then the resulting spray after injection breeds part of the same class of distributions. A spray combustion model is being researched to include more standard size distributions including the effects of droplet interactions and the relative movement of droplets and air, which can affect the engine's combustion characteristics. Numerical investigation of spray structure gives the immense knowledge on spray behaviors inside the combustion chamber.